Analisis Yuridis Penggunaan Purchase Order (PO) terhadap Legalitas Pembelian Mesin Produksi: Studi Kasus Putusan Mahkamah Agung Nomor 1506 K/Pdt/2002 dan Putusan Pengadilan Negeri Cikarang Nomor 76/Pdt.G/2022/Pn Ckr - Ade Winarni (Jurnal Hukum Lex Generalis, 2026)
The purpose of this study is to examine, from a juridical perspective, how the use of a Purchase Order affects the legality of purchasing production machinery and to analyze the liability of the buyer of production machinery in the event of default. This normative legal research employs a statutory approach, a conceptual approach and a jurisprudential approach. To strengthen the analysis, the primary legal materials used include Supreme Court Decision Number 1506 K/Pdt/2002 and Cikarang District Court Decision Number 76/Pdt.G/2022/PN Ckr, as well as provisions of the Indonesian Civil Code, particularly those related to agreements and default. According to the study's findings, as long as an agreement satisfies the conditions outlined in Article 1320 of the Indonesian Civil Code, a purchase that is accepted and executed by the seller demonstrates the existence of an agreement between the parties and creates a legal relationship that gives rise to rights and obligations. In the event that the buyer of production machinery fails to fulfill the payment obligation in accordance with the Purchase Order, the buyer may be deemed to be in default and held legally liable in the form of compensation, specific performance, or termination of the agreement in accordance with applicable legal provisions. This study finds that the purchase of production machinery using a Purchase Order is legally valid. However, to provide legal certainty and optimal legal protection, especially in high-value transactions, a Purchase Order should be accompanied by a written agreement that clearly defines the rights and obligations of each party. Thus, the interests of both buyers and sellers can be balanced in business transaction practices, thereby reducing the risk of legal disputes.